2015
DOI: 10.1007/s10509-015-2473-6
|View full text |Cite
|
Sign up to set email alerts
|

On the limit between short and long GRBs

Abstract: Two classes of GRBs have been identified thus far without doubt and are prescribed to different physical scenarios-NS-NS or NS-BH mergers, and collapse of massive stars, for short and long GRBs, respectively. The existence of two distinct populations was inferred through a bimodal distribution of the observed durations T 90 , and the commonly applied 2 s limit between short and long GRBs was obtained by fitting a parabola between the two peaks in binned data from BATSE 1B. Herein, by means of a maximum likelih… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
32
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(38 citation statements)
references
References 46 publications
(66 reference statements)
6
32
0
Order By: Relevance
“…However, the statistical significance of all the three tests is marginal, thus implying that both hypothesis cannot be easily distinguished. Our results also agree with the analysis of Tarnopolski (2015), who also compared χ 2 probabilities by carrying out a binned analysis of the duration distribution. He concluded that although the χ 2 probability for a 3-component fit is more than a 2-component one, the p-values range from 14-77% for different values of the binning.…”
Section: Fermi-gbmsupporting
confidence: 89%
See 3 more Smart Citations
“…However, the statistical significance of all the three tests is marginal, thus implying that both hypothesis cannot be easily distinguished. Our results also agree with the analysis of Tarnopolski (2015), who also compared χ 2 probabilities by carrying out a binned analysis of the duration distribution. He concluded that although the χ 2 probability for a 3-component fit is more than a 2-component one, the p-values range from 14-77% for different values of the binning.…”
Section: Fermi-gbmsupporting
confidence: 89%
“…In summary, we can say that the preferred model at first look is the k = 2 model for the intrinsic GRB case but its significance is low with all the model comparison tests used. When a similar analysis of the intrinsic T90 distribution of 347 Swift GRBs was done by Tarnopolski (2016b), he found that AIC points to three components (albeit with very weak evidence against two), and BIC yielded a very strong support for two components. The GMMbased analysis also showed evidence for two components with ∆BIC of about 6 (Zhang et al 2016b).…”
Section: Swift Grbs In Rest Framementioning
confidence: 95%
See 2 more Smart Citations
“…On the other hand, this elusive intermediate class might be a statistical feature that can be explained by modeling the duration distribution with skewed distributions, instead of the commonly applied standard Gaussians [57][58][59][60][61]. Additionally, GRB classification was shown to be detector-dependent [1,62,63]. Moreover, a subclass classification of LGRBs was proposed [64], and Norris and Bonnell [65] discovered the existence of an intermediate class or SGRBs with extended emission, that show mixed properties between SGRBs and LGRBs.…”
Section: Introductionmentioning
confidence: 99%